1995
DOI: 10.1113/expphysiol.1995.sp003841
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synovial PO2 and sympathetic vasoconstrictor responses in normal and acutely inflamed rabbit knee joints

Abstract: SUMMARYExperiments were performed to assess the effect of acute inflammation of the rabbit knee joint on the partial pressure of oxygen in synovial fluid (P0o) and nerve-mediated vasoconstrictor responses of articular blood vessels. With the hypodermic needle oxygen electrode sited within the synovial cavity in the posterior region of the knee joint, mean (± S.E.M.) P 02 was 37-4 + 3-6 mmHg (n = 10) in the inflamed group, which differed significantly (P < 0.05) from that occumng in the normal group from a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Using the 133 Xe clearance technique, Dick and colleagues (1971) obtained evidence for a contribution from both á_ and â_adrenergic mechanisms to the regulation of blood flow in normal and diseased human articular vascular beds. Our previous study showed a significant reduction in the efficacy of the sympathetic nervous system in regulating blood flow to the inflamed joint (Najafipour & Ferrell, 1995), a possible explanation for the significantly higher blood flow observed in this condition. Further investigations revealed that although prostaglandins have a role to play in the regulation of basal blood flow to the inflamed joint but they do not appear to play a significant role in the modulation of sympathetic vasoconstriction responses (Najafipour & Ferrell, 1994).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Using the 133 Xe clearance technique, Dick and colleagues (1971) obtained evidence for a contribution from both á_ and â_adrenergic mechanisms to the regulation of blood flow in normal and diseased human articular vascular beds. Our previous study showed a significant reduction in the efficacy of the sympathetic nervous system in regulating blood flow to the inflamed joint (Najafipour & Ferrell, 1995), a possible explanation for the significantly higher blood flow observed in this condition. Further investigations revealed that although prostaglandins have a role to play in the regulation of basal blood flow to the inflamed joint but they do not appear to play a significant role in the modulation of sympathetic vasoconstriction responses (Najafipour & Ferrell, 1994).…”
mentioning
confidence: 73%
“…Alterations in blood flow (and also blood pressure) are expressed as the percentage change from control values measured immmediately before each test procedure. The biological zero values were measured as described previously (Najafipour & Ferrell, 1995) and subtracted from the flow values before calculation of percentage changes in blood flow. Mean arterial pressure was calculated by adding one-third of pulse pressure to the diastolic pressure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations